2018
DOI: 10.7287/peerj.preprints.26895v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water mites (Acari, Hydrachnidia) of riparian springs in a small lowland river valley: what are the key factors for species distribution?

Abstract: This paper examines the impact of disturbance factors -flooding and desiccation -on the distribution of water mites in the riparian springs situated in the valley of a small lowland river, the Krąpiel. The landscape factors and physicochemical parameters of the water were analysed in order to gain an understanding of the pattern of water mite assemblages in the riparian springs. Three limnological types of springs were examined (helocrenes, limnocrenes and rheocrenes) along the whole course of the river and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Therefore, the conservation of valuable springs along large rivers will also require the management of the surrounding terrestrial environment. A recent study by Zawal et al () stressed the positive impact of the anthropogenic transformation of the river valley: preventing the riparian springs from flooding stabilizes the conditions in these habitats, which allows crenobiontic species to persist. Nash, Tecle, and Craig () demonstrated that restoration efforts such as stream re‐channelization positively influenced the Hoxworth springs in the Lake Mary catchment in northern Arizona, by stabilizing the stream width and water retention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conservation of valuable springs along large rivers will also require the management of the surrounding terrestrial environment. A recent study by Zawal et al () stressed the positive impact of the anthropogenic transformation of the river valley: preventing the riparian springs from flooding stabilizes the conditions in these habitats, which allows crenobiontic species to persist. Nash, Tecle, and Craig () demonstrated that restoration efforts such as stream re‐channelization positively influenced the Hoxworth springs in the Lake Mary catchment in northern Arizona, by stabilizing the stream width and water retention.…”
Section: Discussionmentioning
confidence: 99%
“…There is no literature evidence on the relationship between ostracod assemblages and the hydrological assessment of a river valley (River Habitat Survey, RHS). Such analyses have been performed for aquatic beetles (Pakulnicka et al, 2016) and water mites (Zawal et al, 2018) in the Krąpiel valley. In the case of beetles, hydrological parameters were responsible for 13.3% of the total variance in species composition, while anthropogenic transformation of the river valley (RHM and HMS) had a positive influence on the crenobiontic water mite fauna.…”
Section: Effects Of Physical and Chemical Water Propertiesmentioning
confidence: 99%
“…Lowland springs are often characterized by stable habitats, with modest changes in hydrological, thermal, chemical, and biological characteristics (De Luca et al, 2014;Rossetti et al, 2020). However, they may be affected by destabilizing factors, such as drought, flooding, and human impact (Rossetti et al, 2005(Rossetti et al, , 2020Pieri et al, 2007;Pakulnicka et al, 2016;Zawal et al, 2018). Individual springs can support a mosaic of microhabitats which results in a high species richness, for which reason springs are sometimes referred to as biodiversity hotspots (Cantonati et al, 2012;Rosati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations